Household's overindebtedness during the COVID-19 crisis: The role of debt and financial literacy - Łukasz Kurowski (Risks, 2021)
The COVID-19 pandemic has shown how important it is to prepare one's own financial budget for the unexpected loss of income. In this dimension, the financial education of the society plays an invaluable role. It allows us to account for events that may adversely affect personal finances in our budget management decisions. Therefore, the aim of the article is to check whether households with a higher level of financial and debt literacy have better management skills from the perspective of a household's budget, which in the face of a crisis reduces the risk of individuals not paying their liabilities. Thus, at the turn of June and July 2020, we conducted surveys among 1300 Polish citizens. Using the multinomial logistic regression, we show that people with a higher financial and debt literacy are less affected by overindebtedness. During the crisis, people who have a higher debt literacy are better prepared to manage credit liabilities; in this situation, financial literacy is less important. In addition, the type of credit experience turned out to be significant. Respondents who have experience with consumer loans (potentially high-margin products) are more likely to have debt repayment problems than those with mortgage loans experiences.
Keywords: D14; D91; G51; G53; 330; coronavirus pandemic; debt literacy; financial literacy; overindebtedness